Implementation of Determining the Cost of Pawn Maintenance in the Review of Sharia Economic Law - Muhammad Syafry Firman Firman; Isman; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The discussion in this study is how the implementation of the determination of the cost of maintaining pawn goods in the review of sharia economic law. The purpose of this research is to find out the determination of the cost of maintaining pawned goods at PT Pegadaian and the analysis of sharia economic law in determining the cost of maintaining pawned goods. The research method used in this research is descriptive qualitative research with data collection conducted through observation and in-depth interviews with the leadership and staff of the Samarinda branch pawnshop. The results showed that the cost of maintaining pawned goods in practice, the costs are charged to the customer and the amount of costs incurred is based on the size of the loan and is termed capital rent but the Pawnshop will compensate according to the collateral if the customer is harmed or the collateral is damaged then it will maintain and take care as well as possible of the valuables that are collateral from the community, pawnshops are still the main choice of the community to pawn their valuables, so that the presence of pawnshops can reduce the development of pawn practices that harm the community. The Islamic economic law review of the implementation of determining the cost of maintaining pawn goods is still not based on sharia principles and is not in accordance with the Fatwa of the National Sharia Council (DSN), this is because the amount of the cost of maintaining pawn goods cannot be determined based on the amount of the loan.